Soybean Aphid (Hemiptera: Aphididae) Response to Soybean Plant Defense: Stress Levels, Tradeoffs, and Cross-Virulence. Issue 1 (1st December 2014) - Enders, Laramy; Bickel, Ryan; Brisson, Jennifer; Heng-Moss, Tiffany; Siegfried, Blair; Zera, Anthony; Miller, Nick
Abstract : A variety of management methods to control the soybean aphid ( Aphis glycines Matsumura) have been investigated since its invasion into North America in 2000, among them plant resistance has emerged as a viable option for reducing aphid damage to soybeans and preventing outbreaks. Plant resistance methods often use natural soybean plant defenses that impose stress on aphids by reducing fitness and altering behavior. Research efforts have heavily focused on identification and development of aphid resistant soybean varieties, leaving much unknown about soybean aphid response to stressful host plant defenses. In this study, we aimed to 1) evaluate lifetime fitness consequences and phenotypic variation in response to host plant-induced stress and 2) investigate whether trade-offs involving fitness costs and/or cross-virulence to multiple antibiotic soybean varieties exists. We compared aphid survival and reproduction during and after a short period of exposure to soybeans with the Rag2 resistance gene and measured aphid clonal variation in response to Rag2 soybeans. In addition, we measured the performance of Rag2 virulent and avirulent aphids on five soybean varieties with various forms of antibiotic resistance. Our results indicate that plant defenses impose high levels of stress and have long-term fitness consequences, even after aphids are removed from resistant plants. We identified one aphid clone that was able to colonize Rag2 among the seven clones tested, suggesting that virulent genotypes may be prevalent in natural populations. Finally, although we did not find evidence of cross-virulence to multiple antibiotic soybean varieties, our results suggest independent mechanisms of aphid virulence to Rag1 and Rag2 that may involve fitness costs.